An investigation of Epstein-Barr Virus (EBV) latency type and MYC gene aberrations in plasmablastic lymphoma diagnosed at Groote Schuur Hospital, Cape Town, South Africa - Kriel, Raymond Frank (Department of Clinical Laboratory Sciences, 2021)
Introduction: Plasmablastic lymphoma (PBL) is a rare, aggressive, AIDS-associated non-Hodgkin lymphoma. The pathogenesis of PBL is incompletely understood, however association with the Epstein-Barr virus (EBV) and the MYC gene, have been identified as important pathogenic mechanisms. Aims and objectives: To characterise the EBV latency in a cohort of patients diagnosed with PBL at Groote Schuur Hospital (GSH), by means of immunohistochemistry. To determine MYC gene aberrations using fluorescent in situ hybridisation (FISH). Materials and methods: The cohort comprised PBL cases diagnosed from 2005-2017. EBER ISH was used to confirm EBV infection. Manual immunohistochemistry using three monoclonal antibodies for EBV latent proteins, (EBNA1, EBNA2 and LMP1) was used to determine the latency type. Manual MYC FISH was performed on all PBL cases using a dual colour break apart rearrangement probe. Results: Forty-nine cases of PBL were included in this study. Forty-one cases were positive for EBER ISH. Thirty-seven (78.7%) cases showed HIV/EBV coinfection. Latency 0 was observed in 29 (70.7%) cases, latency 1 in 8 (19.5%) and latency 2 in 4 (9.8%) cases. MYC FISH was performed on all 49 PBL cases, of which 30 (61.2%) yielded a result. MYC was intact in 11 (36.7%), translocated in 8 (26.7%) and 11 (36.7 %) cases showed copy number variations. Conclusion: Our research demonstrated 37 (90.2%) of the EBV positive PBL cases showed a restricted latency pattern of 0 or 1. Furthermore we found that MYC gene aberrations consisting of translocations and copy number variations occurred in 19 cases (63.3%) , with copy number variations being higher than cited in current literature. Our study is also the first to investigate PBL EBV latency in SA. An uncommon finding was the existence of MYC gene aberrations in HIV positive, EBV negative PBL cases.